DUKUNGAN SOSIAL DAN BEBAN PENGASUH DENGAN MEDIASI EFIKASI DIRI FAMILY CAREGIVER ODAPUS - Anisa, Syarifah N.; Rahmania, Farra Anisa; Mulyati, Rina (Universitas Gunadarma, 2024)
Lupus not only brings an impact on the people suffering from it but also gives a burden for the family as the main treatment unit for the people with Lupus. Social support from family, friends or closest people is assumed to be able to grow the self-confidence of a family caregiver in coping with any drawbacks in caregiving as it can lessen the burden. This study specifically aimed to observe the impacts of the support of family, friends and closest people on the burden of caregiver through the mediator of self-efficacy to the family caregiver of people with Lupus. This article is a part of the thesis using the quantitative approach with family caregivers of people with Lupus as the research respondents (N=72). The research data collection was carried out online using Zarit Burden Interview, Multidimensional Scale of Perceived Social Support, and Caregiver Self-Efficacy Measures. Data were analyzed by means of mediation analysis technique through JASP. The results of the study showed that self-efficacy only acted as a mediator for the relation between family support and the burden of the caregiver. Family support is a very important factor to increase caregiver self-efficacy which in turn can reduce the care burden for family caregivers.